(3NHQGJ eGdjI hTQYjIs - (3MSGe GdOjf(B, (3eMeOs; (3MGeO(B, (3GdYWGQs ((3HjQhJ(B:s (3GdOGQ GdYQHjI ddYdhe(B,s, 2006)
(3Cda HGA GdHhQUI,fUGFM hNHQGJ ddJOGhd,GdVhGHW GdTQYjI ddJYGed eY GdHhQUI,CHQR aJGhi GdHhQUI,GdHhQUI(B..(3ShLs
Keywords: (3GdChQGb GdeGdjIs; (3GdGSJKeGQs; (3GdHhQUGJs